Glucocorticoid-Induced Leucine Zipper: A Novel Anti-inflammatory Molecule - Bereshchenko, Oxana; Migliorati, Graziella; Bruscoli, Stefano; Riccardi, Carlo (Frontiers in Pharmacology, 2019)
Glucocorticoids (GCs) are the most commonly used drugs for treatment of autoimmune and inflammatory diseases. Their efficacy is due to their ability to bind cytoplasmic receptors (glucocorticoid receptors, GR) and other cytoplasmic proteins, thus regulating gene expression. Although GCs are potent life-saving drugs, their therapeutic effects are transitory and chronic use of GCs is accompanied by serious side effects. Therefore, new drugs are needed to replace GCs. We have identified a gene, glucocorticoid-induced leucine zipper (GILZ or tsc22d3), that is rapidly and invariably induced by GCs. Human GILZ is a 135-amino acid protein that mediates many GC effects, including inhibition of the NF-κB and MAPK pathways. Similar to GCs, GILZ exerts anti-inflammatory activity in experimental disease models, including inflammatory bowel diseases and arthritis. While transgenic mice that overexpress GILZ are more resistant, GILZ knockout mice develop worse inflammatory diseases. Moreover, the anti-inflammatory effect of GCs is attenuated in GILZ-deficient mice. Importantly, in vivo delivery of recombinant GILZ protein cured colitis and facilitated resolution of lipopolysaccharide-induced inflammation without apparent toxic effects. A synthetic GILZ-derived peptide, corresponding to the GILZ region that interacts with NF-κB, was able to suppress experimental autoimmune encephalomyelitis. Collectively, these findings indicate that GILZ is an anti-inflammatory molecule that may serve as the basis for designing new therapeutic approaches to inflammatory diseases.